Isolation and characterization of gut bacteria associated with the degradation of host-specific terpenoids in Pagiophloeus tsushimanus (Coleoptera: Curculionidae) larvae. Issue 2 (19th April 2023) - Qiao, Heng; Zhu, Han; Li, Hui; Chen, Hongjian; Li, Shouyin; Chen, Cong; Hao, Dejun
Abstract: Insect intestinal bacteria play an important role in resisting defensive substances of host plants. Pagiophloeus tsushimanus (Coleoptera: Curculionidae) feeds exclusively on camphor trees ( Cinnamomum camphora, Laurales: Lauraceae) in China, causing substantial economic and ecological losses. It is unclear how the larvae of P. tsushimanus outcome the main secondary metabolites of C. camphora such as D -camphor, eucalyptol, and linalool. In this study, we isolated terpenoid-degrading bacteria from the gut of P. tsushimanus larvae by using selective culture medium. Maximum likelihood phylogenetic analyses were performed with 16S rDNA sequences to identify the bacteria, and results showed ten strains belonged to four genera, including Pseudomonas, Enterobacter, Serratia, and Corynebacterium . Then, gas chromatography was employed to determine the degradability of D -camphor, eucalyptol, and linalool by the isolated strains, results showed that Z5 strain (i.e., Corynebacterium variabile, Actinomycetales: Corynebacteriaceae), F1 strain (i.e., Pseudomonas aeruginosa, Pseudomonadales: Pseudomonaceae), and A3 strain (i.e., Serratia marcescens, Enterobacterales: Enterobacteriaceae) had the highest degradation rates of D -camphor, linalool, and eucalyptol, respectively. The intestinal bacteria were capable of terpenoid degradation in vitro, which suggested that these gut bacteria associated with P. tsushimanus play an important role in overcoming host plant secondary metabolite defense, thereby facilitating the host specialization of this pest.